Analisis Penilaian Ranah Kognitif dalam Perspektif Islam - Samsul Huda; Ainun Fitri Yadi (Primer Edukasi Journal, 2023)
The research is motivated by a lack of educators' understanding of cognitive assessment. In general, education in Indonesia plays a very important role for the state and nation in ensuring survival. Education is an investment for humans so that they can become and create decent human beings in society, especially in the country. Islam views evaluation as very important, because in Islam the factors of measurement, assessment, and achievement of a worship can be seen from the terms and harmony of the worship. A good teaching and learning process must be preceded by good preparation. Therefore, before teaching, the teacher should prepare a learning plan or device. The method in this research uses a study of literature by collecting references consisting of several previous studies. The cognitive domain is a realm related to knowledge. Bloom divides the cognitive domain into 6 levels from the lowest ability to the maximum ability, namely: knowing, understanding, applying, analyzing, evaluating, synthesizing (creating)